Using Omics to Understand and Treat Pulmonary Vascular Disease - Hemnes, Anna R. (Frontiers in Medicine, 2018)
Pulmonary arterial hypertension (PAH) is a devastating disease for which there is no cure. Presently this condition is differentiated from other diseases of the pulmonary vasculature by a practitioner’s history, physical examination and clinical studies with clinical markers of disease severity primarily guiding therapeutic choices. New technologies such as next generation DNA sequencing, high throughput RNA sequencing, metabolomics and proteomics have greatly enhanced the amount of data that can be studied efficiently in patients with PAH and other rare diseases. There is emerging data on the use of these “Omics” for pulmonary vascular disease classification and diagnosis and also new work that suggests molecular markers, including Omics, may be used to more efficiently match patients to their own most effective therapies. This review will focus on the state of knowledge on molecular classification and treatment of PAH. Strengths and weaknesses of current Omic technologies will be discussed and how these new technologies can be used in the future to improve diagnosis of pulmonary vascular disease, more effectively treat patients with existing and future drugs, and generate new understanding of disease pathogenesis and mechanisms underlying treatment success or failure. Recent publications on the use of Omics to diagnose and treat pulmonary arterial hypertension will be discussed and placed in the context of current and future clinical care.